Electropsun Polycaprolactone Fibres in Bone Tissue Engineering: A Review - Siddiqui, Nadeem; Kishori, Braja; Rao, Saranya; Anjum, Mohammad; Hemanth, Venkata; Das, Swati; Jabbari, Esmaiel (Molecular biotechnology, 2021)
Regeneration of bone tissue requires novel load bearing, biocompatible materials that support adhesion, spreading, proliferation, differentiation, mineralization, ECM production and maturation of bone-forming cells. Polycaprolactone (PCL) has many advantages as a biomaterial for scaffold production including tuneable biodegradation, relatively high mechanical toughness at physiological temperature. Electrospinning produces nanofibrous porous matrices that mimic many properties of natural tissue extracellular matrix with regard to surface area, porosity and fibre alignment. The biocompatibility and hydrophilicity of PCL nanofibres can be improved by combining PCL with other biomaterials to form composite scaffolds for bone regeneration. This work reviews the most recent research on synthesis, characterization and cellular response to nanofibrous PCL scaffolds and the composites of PCL with other natural and synthetic materials for bone tissue engineering.